A vulnerabilidade e o racismo ambiental no Brasil: uma análise a partir da perspectiva biopolítica Foucaultiana - Abreu, Ivy de Souza (2018)
The present work proposes to analyze vulnerability and environmental racism in Brazil from the perspective of biopolitics and biopower in Michel Foucault. For this, the contemporary environmental crisis will be discussed, with reflection on fundamental rights and the relationship between human and nature from the point of view of anthropocentrism, biocentrism and holism, and the analytical category environmental racism in the light of concepts of human and environmental vulnerability under the foucaultian prism of biopolitics and biopower based on the foundations of environmental bioethics. Environmental vulnerability, environmental racism, social inequality and exclusion will also be analyzed as an affront to fundamental human rights based on conflicts of power and as elements for reflection on deep ecology. There will also be an analysis of the interconnections between public policies that support of the environmental racism, human and environmental vulnerability and the breaking of the Fundão dam in Mariana-MG in the year 2015 in the light of the concepts of biopower and biopolitics. Environmental racism is a social and environmental problem that demands elucidation and theoretical and practical deepening. The definition of environmental racism still needs to be built, especially in peripheral realities, since extreme economic inequality and the social gap, the damage to fundamental rights, the historical-cultural-degrading heritage of european coloniality, and the powerful tentacles of capitalism in public and private spheres are factors that have propitiated an environmental racism of Latin America and Brazil.